1986
DOI: 10.1017/s0022112086002318
|View full text |Cite
|
Sign up to set email alerts
|

Airfoils with separation and the resulting wakes

Abstract: A viscous/inviscid interaction method is described and has been used to calculate flows around four distinctly different airfoils as a function of angle of attack. It comprises an inviscid-flow method based on conformal mapping, a boundary-layer procedure based on the numerical solution of differential equations and an algebraic eddy viscosity. The results are in close agreement with experiment up to angles close to stall. In one case, where the airfoil thickness is large, small difficulties were experienced a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

1986
1986
1997
1997

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(26 citation statements)
references
References 23 publications
(26 reference statements)
0
25
0
Order By: Relevance
“…If there is no wall transpiration, 1/Jw = 0, then the boundary conditions (21) given in equations (20) and (21) revert back to those given in equation (16).…”
Section: Transition Predictionmentioning
confidence: 99%
“…If there is no wall transpiration, 1/Jw = 0, then the boundary conditions (21) given in equations (20) and (21) revert back to those given in equation (16).…”
Section: Transition Predictionmentioning
confidence: 99%
“…For the purpose of estimating viscous corrections, each computational span station is treated as being locally two dimensional, and the boundary layer computed using Cebeci's inverse technique. 14 ' 15 An equivalent blowing velocity is obtained and used as a correction to the normal boundary condition to account for the addition or subtraction of mass flux through the surface to simulate the growth or decay of the displacement thickness on the wing surface. Any viscous effects on the wake are not accounted for in the present formulation.…”
Section: Viscous Effectsmentioning
confidence: 99%
“…The need to include the wake as part of the calculation at higher angles of attack has been demonstrated by Cebeci et al 3 , who also showed that interaction between the inviscid-and viscous-flow solutions was necessary at the higher angles of attack and at any angle where separated flow existed. As a consequence, the interactive boundary-layer approach described in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…It assumes that transition starts when a small disturbance is introduced at a critical Reynolds number and is amplified by a factor of e 9 or about 8 x 10 3 : the effect of freestream turbulence can be represented by where n = -8.43-2.4£nr T = (3) as proposed by Mack. 10 The amplitude at a fixed point is independent of time and the spatial theory provides the required amplitude change.…”
Section: Introductionmentioning
confidence: 99%